The Smart Coop: Revolutionizing Chicken Care with Automation - Kuhanraj, Kuhanraj A/L Kandarsamy; SUMAIYA BINTI MASHORI, SUMAIYA BINTI MASHORI (Progress in Engineering Application and Technology, 2024)
This study presents "The Smart Coop" to innovate chicken farming in Malaysia by addressing challenges like resource scarcity and high operational costs. Using automated systems, it aims to improve livestock conditions and implement machine learning for eco-friendly food production. Broiler farming in closed systems faces issues like increased costs, storm damage vulnerability, and disease outbreaks, worsened by poor waste management. "The Smart Coop" proposes autonomous monitoring of various factors and integrating air filters for better environmental quality. The project seeks to create a smart chicken coop monitoring and controlling various aspects, incorporating eco-friendly elements like air filters and rainwater collection, and evaluating the system’s reliability. The research methodology includes a literature review, case studies, and practical implementation with Arduino UNO. Performance testing involves temperature control, safety measures, and feeding automation. Findings indicate the smart coop maintains optimal conditions for chicken welfare. Sensors regulate temperature and ensure security, while automated systems promote healthy growth. The air filter eliminates odors, and the air cooler maintains a comfortable environment. While the cleaning system needs improvement, the coop overall meets its objectives. "The Smart Coop" shows potential in improving chicken welfare, reducing environmental impact, and supporting sustainable poultry farming in Malaysia, with suggestions for further optimization